Metadata interoperability requirements for aggregating Islamic manuscript bibliographic records - Sarif Abdullah, Sharifah Nur Amirah; Mansor, Yushiana (Institute of Electrical and Electronics Engineers Inc., 2014)
The advancement in ICT has facilitated the access to rare, valuable, Islamic heritage resources such as manuscripts. Efforts to preserve and disseminate information about precious Islamic manuscripts have been evidenced through initiatives such as digital library projects and online catalogs. Accessibility to Islamic manuscripts housed in various repositories in institutions around the world can be enhanced through the creation of a central gateway interface. This requires the aggregation of bibliographic records surrogating the manuscripts. However, metadata interoperability has been found to be an important determinant in successful records aggregation. This paper discusses factors affecting metadata interoperability among various repositories housing Islamic manuscript from around the world. It also proposes to investigate how library professionals and users view metadata standards, and the issues associated with metadata interoperability in order to establish a shareable metadata for Islamic manuscripts.